Management městského obvodu Pardubice III - Buriancová, Kateřina (Univerzita Pardubice, 2006)
Práce pojednává o managementu konkrétního objektu veřejné správy – Úřadu městského obvodu Pardubice III. V první části, která je částí teoretickou, je popsána problematika managementu, veřejné správy, managementu ve veřejné správě apod. V druhé části popisuji management Městského obvodu Pardubice III včetně analýzy a hodnocení managementu Úřadu městského obvodu.

This work concerns on the management of specific subject of the public administration – the Municipal district office Pardubice III. In the first part, which is theoretical part, there is explained an issue of management, public administration, management in public administration etc. In the second part, there is described management of the Municipal district Pardubice III including analysis and evaluations of the Municipal district office.
Management of the district Pardubice III
Keywords: Management; Public Administration; municipal districts; Management; městské obvody; benchmarking; expertní šetření; SWOT analýza; veřejná správa